Anatomical Pathology of the Umbilical Cord and Its Maternal and Fetal Clinical Associations in 434 Newborns (2018)
Introduction: Umbilical cord (UC) abnormalities and their clinical relations in 434 newborns were analyzed. We had previously reported on clinical associations of long and short UCs with any kind of malformation. This study focuses on other UC features (insertion, vessels, entanglements, coiling, and knots) and their associations with clinical characteristics and neonatal prognosis. Methods: An observational analytic study was performed on placentas from consecutive deliveries. Ordered logistic regression with bivariate and multivariate analysis was performed to evaluate the relationship between variables of interest concerning UC abnormalities. Results: A total of 434 placentas made up the study. UC abnormalities were abnormal insertion, 82 (18.86%); coiling (hypo and hypercoiled), 177 (40.78%); single umbilical artery (SUA), 4 (0.92%); entanglements, 8 (1.84%); true knots, 3 (0.69%); webs in UC base, 9 (2.07%); and right twist, 68 (15.67%). After analyzing maternal and fetal complications during pregnancy, multivariate analysis confirmed the recognized association between malformations and SUA and male gender; further confirmation was also made between hypertensive disorders of pregnancy and true knots. Discussion: UC abnormalities associated with undesirable outcomes are varied and should be recognized and described. Clinical factors associated with anatomical UC abnormalities are not completely understood and justify forthcoming studies. © 2018, Society for Pediatric Pathology All rights reserved.